ROLES OF AUTO-CORRECTION TOOLS ON HUMSS STUDENTS’ WRITING SKILLS - T. Sanchez, Avigail; R. Arcila, Kairille France; L. Baldomero, Jerime; P. Cahanding, Kianna Mhae; A. De Leon5, Rachelle Anne; A. Samson, Catherine (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Auto-correction tools, a product of technological advancement, are now prevalent globally, present and impacting diverse fields. In education, writing is an essential macro skill that an individual must possess or learn and has been transformed by modern learning modalities. Thus, this research paper highlighted the roles of auto-correction tools on the students' writing abilities affecting the variation of their actual English compositions in terms of frequency of errors in vocabulary, in syntax, and in mechanics of writing. Employing a concurrent triangulation mixed method research design, quantitative and qualitative data were analyzed individually and then combined during interpretation. Results reveal that 44% of respondents scored within the